Application Of Model-Based Learning To The Social And Emotional Development Of Early Childhood - Delta Ullu; Metri Ameliana Taneo; Resty Taneo; Maria Yoaknia Taneo; Sintya Binti Fola Besi; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Background: Social-emotional development is a fundamental aspect of early childhood education because it influences children's ability to regulate emotions, cooperate with peers, communicate effectively, and adapt to their learning environment. Objective: This study aimed to examine the effect of the Problem-Based Learning (PBL) model on the social-emotional development of children aged 5–6 years at TK GMIT Sion Camplong. Method: A quantitative study employing an ex post facto design was conducted involving 20 children selected through total sampling. Data were collected using structured observation instruments measuring children's social-emotional development and were analyzed using descriptive statistics and simple linear regression with SPSS version 25. Results: The findings demonstrated that the implementation of the Problem-Based Learning model had a positive and statistically significant effect on children's social-emotional development (p < 0.05). The coefficient of determination (R² = 0.119) indicated that the PBL model explained 11.9% of the variance in children's social-emotional development, while the remaining 88.1% was influenced by other factors beyond the scope of this study. Improvements were observed in children's cooperation, emotional regulation, self-confidence, empathy, and social interaction during classroom activities. Novelty: This study provides empirical evidence regarding the implementation of Problem-Based Learning within an authentic early childhood classroom context to strengthen social-emotional competencies. Conclusion: Problem-Based Learning is an effective child-centered instructional approach for promoting the social-emotional development of children aged 5–6 years.